Finite-Element Analysis of Stress on Dental Implant Prosthesis - Rubo, Jose Henrique; Sousa, Edson Antonio Capello [UNESP] (Wiley-Blackwell, 2010)
Background:Understanding how clinical variables affect stress distribution facilitates optimal prosthesis design and fabrication and may lead to a decrease in mechanical failures as well as improve implant longevity.Purpose:In this study, the many clinical variations present in implant-supported prosthesis were analyzed by 3-D finite element method.Materials and Method:A geometrical model representing the anterior segment of a human mandible treated with 5 implants supporting a framework was created to perform the tests. The variables introduced in the computer model were cantilever length, elastic modulus of cancellous bone, abutment length, implant length, and framework alloy (AgPd or CoCr). The computer was programmed with physical properties of the materials as derived from the literature, and a 100N vertical load was used to simulate the occlusal force. Images with the fringes of stress were obtained and the maximum stress at each site was plotted in graphs for comparison.Results:Stresses clustered at the elements closest to the loading point. Stress increase was found to be proportional to the increase in cantilever length and inversely proportional to the increase in the elastic modulus of cancellous bone. Increasing the abutment length resulted in a decrease of stress on implants and framework. Stress decrease could not be demonstrated with implants longer than 13 mm. A stiffer framework may allow better stress distribution.Conclusion:The relative physical properties of the many materials involved in an implant-supported prosthesis system affect the way stresses are distributed.
Keywords: finite-element analysis; implant prosthesis; stress distribution